Fishes : an introduction to ichthyology - Moyle, Peter B. (Pearson, 2004)
This book provides a comprehensive and current source of information on fishes-including systematics, zoogeography, behavior, and conservation of fishes-that is often needed by professionals as background for writing accurate reports. This book covers the structure and physiology, evolution and taxonomy, zoogeography, and ecology and conservation of fishes. For fisheries biologists, conservation biologists, and aquatic ecologists that need an up-to-date reference on Ichthyology.